Towards a multi‐element silicon drift detector system for fluorescence spectroscopy in the soft X‐ray regime. (20th March 2017) - Bufon, Jernej; Gianoncelli, Alessandra; Ahangarianabhari, Mahdi; Altissimo, Matteo; Bellutti, Pierluigi; Bertuccio, Giuseppe; Borghes, Roberto; Carrato, Sergio; Cautero, Giuseppe; Cicuttin, Andres; Crespo, Maria Liz; Fabiani, Sergio; et al.
Abstract : In spite of the constant technological improvements in the field of detector development, X‐ray fluorescence (XRF) in the soft X‐ray regime remains a challenge. The low intrinsic fluorescence yield for energies below 2 keV indeed renders the applicability of low‐energy XRF still difficult. Here, we report on a new multi‐element multi‐tile detection system currently under development, designed to be integrated into a soft X‐ray microscopy end station. The system will be installed at the TwinMic beamline of Elettra synchrotron (Trieste, Italy) in order to increase the detected count rate by up to an order of magnitude. The new architecture is very versatile and can be adapted to any XRF experimental setup. Even though the first results of the previous version of such a multi‐element system were encouraging, several issues still needed to be addressed. The system described here represents a further step in the detector evolution. It is based on four trapezoidal‐shaped monolithic silicon drift detector tiles (matrices) with six hexagonal elements each equipped with a custom ultra‐low noise application‐specific integrated circuit readout. The whole signal processing chain has been improved leading to an overall increase in performances, namely, in terms of energy resolution and acquisition rates. The design and development of this new detection system will be described, and recent results obtained at the TwinMic beamline at Elettra will be presented. Future perspectives and improvements will also be discussed. Copyright © 2017 John Wiley & Sons, Ltd.